A sustainable business model for Open-Access journal publishing: a proposed plan for High-Energy Physics - Vigen, Jens (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
The High Energy Physics community over the last 15 years has achieved so-called full green Open Access through the wide dissemination of preprints via arXiv, a central subject repository managed by Cornell University. However, green Open Access does not alleviate the economic difficulties of libraries as they are still expected to offer access to versions of record of the peer-reviewed literature. For this reason the particle physics community is now addressing the issue of gold Open Access by converting a set of the existing core journals to Open Access. A Working Party has been established to bring together funding agencies, laboratories and libraries into a single consortium, called SCOAP3 (Sponsoring Consortium for Open Access Publishing in Particle Physics). This consortium will engage with publishers to build a sustainable model for Open Access publishing. In this model, subscription fees from multiple institutions are replaced by contracts with publishers of Open Access journals, where the SCOAP3 consortium is a single financial partner.